COMMUNITY SERVICE STRATEGY: OPTIMISING THE POTENTIAL OF MSMEs IN THE VILLAGE - Wulandari Wulandari; Maryati; Oskar Hutagaluh (Adiba Aisha Amira, 2024)
Community service that focuses on optimising the potential of Micro, Small and Medium Enterprises (MSMEs) in villages is a strategic step to improve the welfare and living standards of local communities. This activity begins with the identification of the potential and constraints faced by MSMEs in the area, followed by a comprehensive analysis that helps map out the most relevant interventions. This approach includes skills training, access to capital, and more effective and efficient marketing of products. The active involvement of local communities in MSME development increases the sense of ownership and responsibility for the sustainability of the programme. Collaboration with the government, educational institutions and the private sector is also crucial to provide holistic support. Various forms of concrete support, such as training, technical assistance, and development of marketing networks, are expected to bring positive impacts to small businesses in villages. In this digital era, the utilisation of information technology is key in expanding market reach and improving operational efficiency of rural MSMEs. The implementation of e-commerce and digital marketing allows MSMEs to access a wider market and market their products nationally and internationally. In addition, technology also provides easier access to important information and resources that can support business development. The success and sustainability of this strategy depends on regular evaluation and the ability to adapt the programme based on the results. Continuous programme adjustments ensure that the strategy remains relevant and effective in the face of changing conditions on the ground. Thus, optimising the potential of MSMEs in the village is expected to have a sustainable positive impact, not only for the business actors, but also for the village economy as a whole.